2019
DOI: 10.1177/0731121419835504
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital’s Influence on Environmental Concern in China: An Analysis of the 2010 Chinese General Social Survey

Abstract: This study examines the ways in which social capital influences people’s environmental concern in China. Using data obtained from the 2010 Chinese General Social Survey, we measure social capital through social networks and trust. We find that the ways people think about and act toward others influence the ways they think about and act toward the environment. The structural equation modeling results suggest that one’s connections with others, including socializing with relatives and friends as well as general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…However, our meta-regression results cannot confirm the significant impact of trust in others on pro-environmental behaviors (see Table 3 ). Some of the existing literature suggests that trust in others may fail to motivate new attitudes about environmental issues and pollution [ 87 ]. In their study, the authors argued that a higher level of trust within a close network could cultivate a sense of comfort and security and thus makes people less likely to respond to less immediate and indirectly observable environmental issues.…”
Section: Resultsmentioning
confidence: 99%
“…However, our meta-regression results cannot confirm the significant impact of trust in others on pro-environmental behaviors (see Table 3 ). Some of the existing literature suggests that trust in others may fail to motivate new attitudes about environmental issues and pollution [ 87 ]. In their study, the authors argued that a higher level of trust within a close network could cultivate a sense of comfort and security and thus makes people less likely to respond to less immediate and indirectly observable environmental issues.…”
Section: Resultsmentioning
confidence: 99%
“…For analysis, multigroup regressions were performed demarcating respondents with a well owner/non-well owner dichotomy. Other scholars have employed similar analyses to look into the effect of moderators for PEBs [46] and environmental concern [47]. Given that my framing hinges on the differences in water provision, this research assesses Kansans' conservation of water within different infrastructural contexts.…”
Section: Data Collection Sample Overview and Methodsmentioning
confidence: 99%
“…Tam and Chan (2018) found that trust effectively strengthens the connection between environmental concerns and environmental actions. Trust has a significant positive impact on environmental behavior in different national contexts (Hao et al, 2019). Thus, it is proposed that: Hypothesis 1b: In China, social trust promotes garbage classification.…”
Section: Social Capital and Garbage Classificationmentioning
confidence: 99%